Integrated environmental mapping and monitoring, a methodological approach to optimise knowledge gathering and sampling strategy. Issue 1 (15th July 2015) - Nilssen, Ingunn; Ødegård, Øyvind; Sørensen, Asgeir J.; Johnsen, Geir; Moline, Mark A.; Berge, Jørgen
Graphical abstract: Highlights: A new methodological approach for integrated environmental mapping and monitoring. Flexible approach adjusted to purpose of mission and object of interest. Appropriate spatial and temporal resolutions of data through the use of different sensor platforms. Use of two practical case studies to explain the systematic approach. Abstract: New technology has led to new opportunities for a holistic environmental monitoring approach adjusted to purpose and object of interest. The proposed integrated environmental mapping and monitoring (IEMM) concept, presented in this paper, describes the different steps in such a system from mission of survey to selection of parameters, sensors, sensor platforms, data collection, data storage, analysis and to data interpretation for reliable decision making. The system is generic; it can be used by authorities, industry and academia and is useful for planning- and operational phases. In the planning process the systematic approach is also ideal to identify areas with gap of knowledge. The critical stages of the concept is discussed and exemplified by two case studies, one environmental mapping and one monitoring case. As an operational system, the IEMM concept can contribute to an optimised integrated environmental mapping and monitoring for knowledge generation as basis for decision making.